How tweets become the news: Using X as a newsgathering tool to report on loadshedding at News24, Netwerk24 and TimesLIVE - Lottering, Lisa Demi (Stellenbosch : Stellenbosch University, 2025)
Thesis (MA)--Stellenbosch University, 2025.